Informacja sprawozdawcza małych i średnich podmiotów gospodarczych - Kaczmarczyk, Angelika (Financial Information of Small And Medium Size Entities, 2007)
The aim of this article is to make an attempt to answer the question: what kinds of features docs financial information in small and medium size entities have or is obligatory financial reporting useful in management of the small and medium economic entities?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 226-232